Mapping of sheep sensory cortex with a novel microelectrocorticography grid. Issue 16 (16th June 2014) - Gierthmuehlen, Mortimer; Wang, Xi; Gkogkidis, Alexis; Henle, Christian; Fischer, Joerg; Fehrenbacher, Thomas; Kohler, Fabian; Raab, Markus; Mader, Irina; Kuehn, Celina; Foerster, Katharina; Haberstroh, Joerg; et al.
ABSTRACT Microelectrocorticography (µECoG) provides insights into the cortical organization with high temporal and spatial resolution desirable for better understanding of neural information processing. Here we evaluated the use of µECoG for detailed cortical recording of somatosensory evoked potentials (SEPs) in an ovine model. The approach to the cortex was planned using an MRI‐based 3D model of the sheep's brain. We describe a minimally extended surgical procedure allowing placement of two different µECoG grids on the somatosensory cortex. With this small craniotomy, the frontal sinus was kept intact, thus keeping the surgical site sterile and making this approach suitable for chronic implantations. We evaluated the procedure for chronic implantation of an encapsulated µECoG recording system. During acute and chronic recordings, significant SEP responses in the triangle between the ansate, diagonal, and coronal sulcus were identified in all animals. Stimulation of the nose, upper lip, lower lip, and chin caused a somatotopic lateral‐to‐medial, ipsilateral response pattern. With repetitive recordings of SEPs, this somatotopic pattern was reliably recorded for up to 16 weeks. The findings of this study confirm the previously postulated ipsilateral, somatotopic organization of the sheep's sensory cortex. High gamma band activity was spatially most specific in the comparison of different frequency components of the somatosensory evoked response. This study provides a basis for further acute and chronic investigations of the sheep's sensory cortex by characterizing its exact position, its functional properties, and the surgical approach with respect to macroanatomical landmarks. J. Comp. Neurol. 522:3590–3608, 2014. © 2014 Wiley Periodicals, Inc.